Influence of social environment on the attitude of senior pupils to religion and atheism - Tidikis , R. (Psichologija, 1969)
The pedagogical and social research work carried out in schools - of the Lithuanian S.S.R. shows that social micro-environment (family) has its influence on the religious and atheistic views of senior pupils and conditions their religious and atheistic activities. The greatest influence on the religiosity of a senior pupil has a family in which both of the parents are pious and systematically celebrate religious festivals observing all the religious rites and ceremonies. But the religious influence of the parents on senior pupils is strongly limited by the atheistic influence of school and other factors and also due to the growth of consciousness and maturity of the pupils themselves. The article reflects the degree of social conditionality and causality of religiosity and atheistic activities of senior pupils.